An adaptation pathways approach to water management and governance of tourist islands: the example of the Southern Aegean Region in Greece. Issue 7 (16th November 2020) - Skrimizea, Eirini; Parra, Constanza
ABSTRACT: Approaches to decision making for adaptation need to be place-centred and to consider the interacting changes that occur at different spatiotemporal scales. Τhe adaptation pathways approach provides an interesting input to this end. In this article, we fine-tune the adaptation pathways considerations to the management and governance of water in tourist islands vulnerable to water stress. We base our analysis on literature on climate change, adaptive Integrated Water Resources Management and governance, water and tourism, and social-ecological systems. We illustrate our theoretical analysis with the example of the Southern Aegean islands in Greece, based on secondary sources and interviews with stakeholders.